Quantitation Of Camptothecin From Ervatamia Heyneana (Wall.) T. Cooke Stem Powder Using High Performance Thin Layer Chromatography - VIDYA DIGHE,; GAURANG PAREKH,; DHANASHRI MESTRY, (International Journal of Pharma and Bio Sciences, 2012)
A sensitive and reliable quantitative high performance thin layer chromatographic method has been developed for the quantitation of camptothecin from the dry stem powder of Ervatamia heyneana (Wall.) T. Cooke. Ervatamia heyneana (Wall.) T. Cooke has anticancer activity [1]. Methanolic extract of the dry stem powder of Ervatamia heyneana (Wall.) T. Cooke was used for carrying out TLC on silica gel 60 F254 plates. Detection and quantitation was performed by densitometric scan in fluorescence, by using mercury lamp at λ = 366 nm. Accuracy of the developed HPTLC method was checked by conducting the recovery study. The average percent content of camptothecin in stem powder of the used plant, as estimated by the proposed method, was found to be 0.041mg/g. The HPTLC method developed for the quantitative determination of camptothecin in Ervatamia heyneana (Wall.) T. Cooke stem powder is rapid, simple and precise.